1988
DOI: 10.1002/arch.940080105
|View full text |Cite
|
Sign up to set email alerts
|

Yolk hydrolase activities associated with polypeptide and oligosaccharide processing of Blattella germanica vitellin

Abstract: Various aspects of the processing of Blattella germanica vitellin (Vt) in the oocyte and egg have been investigated. Employing subunit specific antibodies, the precursor product relationships among t h e subunits of this Vt have been determined. After endocytosis of Vt by the oocyte, t h e M, 160,000 subunit Vt is cleaved to products of M, 95,000 and M, 50,000. In association with an unprocessed M, 102,000 peptide, these form the subunits of the Vt of freshly ovulated eggs. Between 4 and 5 days post ovulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 38 publications
3
40
0
Order By: Relevance
“…Unique limit peptides in vitro were M r 88,000, 70,000, and 50,000 -53,000. Processing of the M r 50,000 subunit in vitro was obscured by other products of that approximate size, but this subunit is processed beginning at day 5 (16,18). Addition of fresh enzyme to the in vitro incubation did not alter the product distribution.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Unique limit peptides in vitro were M r 88,000, 70,000, and 50,000 -53,000. Processing of the M r 50,000 subunit in vitro was obscured by other products of that approximate size, but this subunit is processed beginning at day 5 (16,18). Addition of fresh enzyme to the in vitro incubation did not alter the product distribution.…”
Section: Resultsmentioning
confidence: 92%
“…Previous work demonstrated that Vt utilization in Blattella germanica eggs is initiated at days 3-4 postovulation by proteolytic processing to a distinct set of peptides, which are then accessed by the embryo during development (9,15,16). Similar processing events are characteristic of Vt utilization in other insect species also (see Ref.…”
mentioning
confidence: 72%
See 3 more Smart Citations